2022
DOI: 10.1002/lno.12180
|View full text |Cite
|
Sign up to set email alerts
|

Water depth and transparency drive the quantity and quality of organic matter in sediments of Alpine Lakes on the Tibetan Plateau

Abstract: Identifying primary environmental drivers mediating the quantity and quality of sedimentary organic matter (OM) in climate-sensitive alpine lakes is crucial to understanding the role of alpine lakes in greenhouse gas emissions and Earth's climate system. Here, we characterized various pools of OM of 20 alpine lakes across the Tibetan Plateau, including bulk OM, water-soluble OM and alkaline-extracted OM from surface sediments, and dissolved OM (DOM) from surface water. The total organic carbon (TOC) content in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…Disentangling the DOM composition and structure, such as microscopic morphology, molecular weight distribution, and chemical bond composition, is essential for understanding its reaction processes and mechanisms and feedback to environmental change. Various DOM characterization methods have been applied to the alpine water quality assessment and the evaluation of anthropogenic effects on DOM-induced biogeochemical cycling (Zhang et al, 2007;Mu et al, 2016;Ma et al, 2018;Wang et al, 2018;Zhou et al, 2019;Li et al, 2020;Du et al, 2022). Different characterization methods have their own advantages and disadvantages for the case of alpine water analysis (Table 1).…”
Section: Methods Comparisonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Disentangling the DOM composition and structure, such as microscopic morphology, molecular weight distribution, and chemical bond composition, is essential for understanding its reaction processes and mechanisms and feedback to environmental change. Various DOM characterization methods have been applied to the alpine water quality assessment and the evaluation of anthropogenic effects on DOM-induced biogeochemical cycling (Zhang et al, 2007;Mu et al, 2016;Ma et al, 2018;Wang et al, 2018;Zhou et al, 2019;Li et al, 2020;Du et al, 2022). Different characterization methods have their own advantages and disadvantages for the case of alpine water analysis (Table 1).…”
Section: Methods Comparisonsmentioning
confidence: 99%
“…Up to November 2023, using alpine (plateau, alpine, or highland), water quality, and dissolved organic matter as keywords, ~500 articles were found in the Web of Science (WOS) database. Further screening found that ~70 papers focused on the DOM analysis and characterization methods for alpine water, among which most papers (~2/3) focused on the Tibetan Plateau (e.g., Hayakawa et al, 2004;Li et al, 2020;Du et al, 2022). Other study areas include Europe (Laurion et al, 2000;Mladenov et al, 2008;Singer et al, 2012), North America (Belzile et al, 2002;Morris and Hargreaves, 2003;Miller et al, 2009), and Antarctica (Guo et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the processing rates of organic C degradation vary regionally and globally (Tiegs et al, 2019), likely arising from the differences in biotic (autotrophic production and heterotrophic microbial degradation) and abiotic (e.g., light) degradation of DOM across large spatial scales. Specifically, environmental factors such as temperature, precipitation, and solar irradiation, have been identified as important regulators of DOM compositions at both region and continental scales (Du et al, 2022(Du et al, , 2023. The variation in microbial community compositions, driven by environmental factors within and across stream ecosystems, also plays a role.…”
Section: Introductionmentioning
confidence: 99%
“…Lake sediments are major sinks of organic matter and serve as pivots for the biogeochemical cycling of nutrients; thus, they are crucial for maintaining the stability and ecological functions of lake ecosystems. Lake sediments worldwide are estimated to contain 820 Pg of organic carbon, and the annual organic carbon burial is 0.2–0.6 Pg C. The accumulated sediment organic matter (SOM) can also be released into the overlying water body , to refuel the ambient nutrient stock, particularly in shallow lakes. Sediment organic nitrogen (SON), an important component of SOM, can be easily ammoniated to produce ammonium (NH 4 + –N), which subsequently supports harmful algal blooms .…”
Section: Introductionmentioning
confidence: 99%